Reducing gastrointestinal tract bleeding in family practice - Herbie R. Schneider (South African Family Practice)
Upper gastrointestinal bleeding occurs commonly. Fortunately, severe life-threatening bleeding is less common, but can be catastrophic, particularly in the elderly patient with co-morbidity such as cardiac or respiratory disease. In order to reduce the risk of bleeding, it is necessary to examine the causes of bleeding and, where possible, modify the risk factors. This review will focus on the prevention of non-variceal upper gastrointestinal bleeding.